1986
DOI: 10.1161/01.cir.73.3.492
|View full text |Cite
|
Sign up to set email alerts
|

Differential long-term intrarenal and neurohormonal effects of captopril and prazosin in patients with chronic congestive heart failure: importance of initial plasma renin activity.

Abstract: Fifty patients with congestive heart failure received, by infusion, 15 ml/kg body weight water load, and systemic hemodynamic, renal function, and neurohumoral parameters values were measured before, 2 days, and 1 month after randomly allocating patients to prazosin or captopril therapy. Both prazosin and captopril caused similar and persistent hemodynamic changes, but important differences existed between their renal and neurohumoral effects. After 1 month of continuous therapy, captopril increased creatinine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1987
1987
1998
1998

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(17 citation statements)
references
References 36 publications
(13 reference statements)
0
17
0
Order By: Relevance
“…[37][38][39][40] This probably reflects an activation of compensatory mechanisms that are thought to be crucial for the maintenance of circulatory function in heart failure.37 Moreover, there was considerable blunting of response to tilting for each agent in proportion to the degree of basal elevation in plasma levels ( Figure 5). Thus, aldosterone, plasma renin activity, and atrial natriuretic peptide, all markedly elevated in heart failure, showed no significant further change in response to postural stress.…”
Section: Discussionmentioning
confidence: 99%
“…[37][38][39][40] This probably reflects an activation of compensatory mechanisms that are thought to be crucial for the maintenance of circulatory function in heart failure.37 Moreover, there was considerable blunting of response to tilting for each agent in proportion to the degree of basal elevation in plasma levels ( Figure 5). Thus, aldosterone, plasma renin activity, and atrial natriuretic peptide, all markedly elevated in heart failure, showed no significant further change in response to postural stress.…”
Section: Discussionmentioning
confidence: 99%
“…Samples which took more than 24 h to reach the central laboratory, or which were haemolyzed or thawed, were not analysed. Previously described neurohormone assays [18,19] were used to measure plasma renin activity and plasma concentrations of norepinephrine, atrial natriuretic peptide, arginine vasopressin, epinephrine, and aldosterone. The pattern of pre-randomization neurohumoral activation and its prognostic significance have been reported previously [2,9] .…”
Section: Patientsmentioning
confidence: 99%
“…Ganglionic blocking drugs and adrenergic antagonists such as phenoxybenzamine improve urinary flow and sodium excretion in CHF (Brod et al 1954;Cannon 1977). It has also recently been shown that the selective al blocker prazosin increases water excretion in patients with CHF, at least in the short term (Mettauer et al 1986). SNS activation also stimulates renin release and enhancement of RAAS activity may also contribute, indirectly, to the role of the SNS in the impaired sodium and water excretion of CHF.…”
Section: Sympathetic Nervous Systemmentioning
confidence: 98%
“…There is accumulating evidence to suggest that the neurohumoral changes alluded to above have a pivotal role to play. In patients matched for similar degrees of left ventricular dysfunction the severity of renal impairment correlates directly with the overall degree of neuroendocrine derangement (Mettauer et al 1986). This suggests that hormonal changes have an independent primary role in the altered kidney function in CHF.…”
mentioning
confidence: 99%